Chemical Profiling, Antioxidant, and Antimicrobial Activity of Saudi Propolis Collected by Arabian Honey Bee (Apis mellifera jemenitica) Colonies - Wed Mohammed Ali ALaerjani; Khalid Ali Khan; Badria M. Al-Shehri; Hamed A. Ghramh; Ajaz Hussain; Mohammed Elimam Ahamed Mohammed; Muhammad Imran; Irfan Ahmad; Saboor Ahmad; Abdulrhman S. Al-Awadi (MDPI AG, 2022)
Propolis (bee glue) is a complex, phyto-based resinous material obtained from beehives. Its chemical and biological properties vary with respect to bee species, type of plants, geographical location, and climate of a particular area. This study was planned with the aim of determining the chemical composition and to investigate various properties (against oxidants and microbes) of different extracts of Saudi propolis collected from Arabian honey bee (Apis mellifera jemenitica) colonies headed by young queens. Chemical analysis of propolis extracts with different solvents, i.e., ethyl acetate (Eac), methanol (Met), butanol (BuT), and hexane (Hex) was done through colorimetry for the total phenolic content (TPC) and total flavonoid content (TFC) evaluation. For separation and extensive characterization of the Met extract, chromatography and 1H NMR were deployed. Six different microorganisms were selected to analyze the Saudi-propolis-based extract's antimicrobial nature by measuring zones of inhibition (ZOI) and minimum inhibitory concentration (MIC). Molecular docking was done by utilizing AutodDock, and sketching of ligands was performed through Marvin Chem Sketch (MCS), and the resultant data after 2D and 3D clean were stored in .mol format. The highest TFC (96.65 mg quercetin equivalents (QE)/g of propolis) and TPC (325 mg gallic acid equivalents (GAE)/g of propolis) were noted for Met. Six familiar compounds were isolated, and recognition was done with NMR. Met extract showed the greatest 1,1-diphenyl-2-picrylhydrazyl radical (DPPH) free radical scavenging activity and Ferric Reducing Antioxidant Power (FRAP). Met showed max microbial activity against Staphylococcus aureus (ZOI = 18.67 mm, MIC = 0.625 mg/mL), whereas the minimum was observed in Hex against E. coli (ZOI = 6.33 mm, MIC = 2.50 mg/mL). Furthermore, the molecular docking process established the biological activity of separated compounds against HCK (Hematopoietic cell kinase) and Gyrase B of S. aureus. Moreover, the stability of protein-ligand complexes was further established through molecular dynamic simulation studies, which showed that the receptor-ligand complexes were quite stable. Results of this research will pave the way for further consolidated analysis of propolis obtained from Arabian honey bees (A. m. jemenitica).